Immunoglobulin G antibodies directed against protein III block killing of serum-resistant Neisseria gonorrhoeae by immune serum (The Rockefeller University Press, 1986)
Neisseria gonorrhoeae that resist complement-dependent killing by normal human serum (NHS) are sometimes killed by immune convalescent serum from patients recovering from disseminated gonococcal infection (DGI). In these studies, killing by immune serum was prevented or blocked by IgG isolated from NHS. Purified human IgG antibodies directed against gonococcal protein III, an antigenically conserved outer membrane protein, contained most of the blocking activity in IgG. Antibodies specific for gonococcal porin (protein I), the major outer membrane protein, displayed no blocking function. In separate experiments, immune convalescent DGI serum which did not exhibit bactericidal activity was restored to killing by selective depletion of protein III antibodies by immunoabsorption. These studies indicate that protein III antibodies in normal and immune human serum play a role in serum resistance of N. gonorrhoeae.